ANALISIS NARATIF TERHADAP LUKAS 15:11-32: KAJIAN INTERVENSIN KRISIS JAMES DAN GILLILAND - Djarang, Gledis; Makiengung, Erci Alicia; Tamamilang, Inkan S (PT. Giat Konseling Nusantara, 2025)
This article intends to analyze more deeply regarding the continued handling of the crisis experienced by the youngest child in the biblical text entitled